The effect of environmental factors on the occurrence and densities of immature stages of Anopheles stephensi (Liston, 1901) and A.pulcherrimus (Theobald, 1902) mosquitoes in Basra city. - Marzoq, Muna K.; Kareem, Dhia K. (Iraqi Journal of Aquaculture, 2021)
The study included collecting monthly samples of the aquatic stage of Anopheles mosquitoes for the period from January 2009 to December 2010 for a number of permanent and temporary stations in Basra city, which included the areas of Al-Faw, Abu Al-Khasib, Shatt Al-Arab, Karma Ali, Al-Sweib and Al-Madina. A range of environmental factors was measured, such as water temperature, salinity, and pH and dissolved oxygen. The monthly changes for a full year showed the effect of these factors on the presence and density of immature stage, so the water of the fixed five sample collection stations tended to be neutral to basic during most of the study period and that it had an oxygen content of 11.2 mg / liter and did not reach the critical limit at any time. The average water temperature ranged from 7.5 to 32.2 degrees, the salinity rates ranged between 2.5 and 5.3 parts per thousand. The results also showed a difference in the distribution and spread of these roles, so it appeared that individuals of the species A. stephensi were more present than the members of the species A.pulcherrimus in Basra city, where the eggs of the A. stephensi appeared in just five months, with a total of 6-25 eggs, and larvae were present in all the study months except for July, the study recorded its highest density in October 2009, which was 277.5 larvae / half liter of water, while the lowest density of 7 larvae / half liter of water was in August, and the virginity density ranged between 1.3-22 virgin / pint of water. Regarding the species A.pulcherrimus, the annual number of eggs ranged between 3-8 eggs, while the highest density of its larvae in March reached 163 larvae / half a liter of water, and the lowest density was recorded at 2/1 pint of water in June and August 2990, and it did not appear in July and September, the annual density of virgins ranged between 0.7 and 19 virgins per liter of water.